Curriculum principles in ICT subjects at Al-Hidayah Primary School - Perdiansah Perdiansah (Hipkin Journal of Educational Research, 2025)
The development of digital technology requires primary education to implement a curriculum that equips students with relevant ICT skills. In this context, this study aims to examine the application of curriculum development principles in the Information and Communication Technology (ICT) subject at Al-Hidayah Primary School, focusing on the principles of relevance, flexibility, continuity, efficiency, and effectiveness. A qualitative approach was used, with data collected through semi-structured interviews conducted online via video calls and direct observation. The results show that the Kurikulum Merdeka implemented in the 2024-2025 academic year includes relevant content, such as digital ethics and social media. Teachers demonstrated adaptive capabilities in designing flexible, continuous learning across grade levels, particularly in grades 4-6. Although there remain limitations in computer equipment, the learning strategies were considered reasonably efficient and effective. These findings emphasize that the success of curriculum implementation largely depends on teachers’ ability to translate curriculum principles into practices that are appropriate to the school context. Therefore, teacher training and support are essential to ensure the sustainability of ICT learning.   Abstrak Perkembangan teknologi digital menuntut pendidikan dasar untuk menghadirkan kurikulum yang mampu membekali murid dengan keterampilan TIK yang relevan. Dalam konteks ini, penelitian ini bertujuan mengkaji penerapan prinsip-prinsip pengembangan kurikulum dalam mata pelajaran Teknologi Informasi dan Komunikasi (TIK) di Sekolah Dasar Al-Hidayah, dengan fokus pada prinsip relevansi, fleksibilitas, kontinuitas, efisiensi, dan efektivitas. Pendekatan kualitatif digunakan dengan pengumpulan data melalui wawancara semi-terstruktur yang dilakukan secara daring melalui video call serta observasi langsung. Hasil penelitian menunjukkan bahwa Kurikulum Merdeka yang diterapkan pada tahun ajaran 2024-2025 telah memuat materi yang relevan, seperti etika digital dan media sosial. Guru menunjukkan kemampuan adaptif dalam menyusun pembelajaran yang fleksibel dan berkesinambungan antar jenjang, terutama di kelas 4 hingga 6. Meskipun masih terdapat keterbatasan perangkat komputer, strategi pembelajaran dinilai cukup efisien dan efektif. Temuan ini menekankan bahwa keberhasilan implementasi kurikulum sangat bergantung pada kemampuan guru dalam menerjemahkan prinsip-prinsip kurikulum ke dalam praktik yang sesuai dengan konteks sekolah. Oleh karena itu, pelatihan dan dukungan terhadap guru menjadi hal penting untuk menjamin keberlanjutan pembelajaran TIK. Kata Kunci: adaptasi teknologi; kurikulum merdeka; kurikulum TIK; prinsip-prinsip kurikulum